Internet based troubleshooting and monitoring system of industrial robots - Rahman, Md Mozasser; Parnin, Sulleha (LAP LAMBERT Academic Publishing, 2017)
This book described an industrial robot monitoring system that is remotely control via internet. The use of industrial robot is increased in small to medium enterprise (SME’s). Many of their processes need to be automated by using robot. The limitations of a programmer to monitor the robot always exist because programmer is not always being in the robot operation area. Thus, a prototype of a monitoring system was developed and tested in the IIUM Robotics laboratory by using small industrial robot. The robot can be monitored by the real time video if there is internet connectivity between the computers in the remote monitoring area and robot operational area. This book is aimed to help in developing a system that capable of connecting programmer with a robot at a remote location. Arduino microcontroller was used to send the signal to the robot from a remote computer. The open source software fit the requirement of this project which enable the development to be completed with a low cost budget. The user interface program is created which enable the programmer to monitor the robot from a remote area by using TeamViewer application. A USB camera is also used to watch the real time video of the robot. All the subsystem is successfully integrated by applying a D3TIC (Define, Data Gathering and Analysis, Develop, Testing, Improve and Conclusion) methodology. The book comprised of 5 chapters. Chapter 1 contains background, objectives, problem statement, methodology, scope of work and the report content. It gives an outer-view of this project, specifies the idea and is a very important to good enough to attract the reader to continue to read. Also, introduction chapters highlighted the interesting methodology used throughout this project in order to define and realize the project goals. Chapter 2 summarized the research done by other people in the range of 10 years back. Only the research that is similar to this project was cited and presented in this project. This is to show the level of this project compare to the other research in terms of its technology and tools and methodology. Chapter 3 covers Project Methodology, conceptual, embodiment and detail design. The conceptual design sub-chapter will again be highlighting the way to define the project problems statement, methodology, project concept generation and the evaluation in selecting the best concept. Meanwhile, embodiment design explains the decision on the hardware selection and its relevancy. Chapter 4 discusses on the works that have been done in order to achieve some of the project objective. The performance of every subsystem was explained in details including the problems faced while handling them. Finally, the performance of the overall system was tested after the subsystems are integrated. The last chapter is as the concluding for this project. It contains summary, achievement of objectives, limitation and challenges with some recommendations for possible improvement of the project.